Outlining three arguments for Rights of Antarctica - Baard, Patrik; Mancilla, Alejandra (The Polar Journal, 2024)
In this article, we investigate three arguments for Rights of Antarctica (RoA), understood as recognising the whole continent as a rights-holder with legal standing. For this, we draw inspiration from the Antarctica Declaration, a text developed by an interdisciplinary and international group of scholars and activists. We scrutinise three justifications that could potentially be used in support of RoA. First, we investigate whether arguments for Rights of Nature (RoN) elsewhere can support RoA. RoN has been accepted in several domestic legislations. Unfortunately, we discover important disanalogies between RoA and RoN, defeating the purpose of justifying RoA with reference to RoN. Second, we scrutinise potential arguments that focus on giving rights to specific Antarctic ecoregions or places. However, such arguments would only cover parts of the continent, thus going against the holistic approach of RoA, and they would require using a broader understanding of ?attachments? as grounds for justifying rights for parts of Antarctica. In contrast, we construct an argument for accepting RoA based on four components: (1) Antarctica?s intrinsic value, (2) wider forms of human attachments, (3) Antarctica?s substantial role as a global systemic resource, and (4) the fact that Antarctica is under recurrent and substantial threats. While none of these are individually sufficient for recognising RoA, they can jointly make RoA appropriate. We conclude that it remains an open question whether international law or, more specifically, the Antarctic Treaty, would be open to such conceptual and normative innovation, adopting a new paradigm in our treatment of the nonhuman natural world. At the same time, we hope to kickstart a discussion of what RoA would require and how it should relate more generally to RoN discourses.
Keywords: Antarktis; Antarktistraktaten; jus

Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

Turned 60, is the Antarctic treaty system in good health? - Mancilla, Alejandra; Jabour, Julia Ann (The Geographical Journal, 2023)
Signed in 1959, the Antarctic Treaty is usually hailed as an example of what states can achieve when they leave aside their interests and truly collaborate. It was over 30?years ago, however, that the last significant legal instrument of the Antarctic Treaty System (namely, the Protocol on Environmental Protection) was signed. Since then, no new legal instruments have been drafted, despite a number of growing internal and external challenges. In this special issue, an interdisciplinary group of scholars examine some of these challenges and evaluate whether the system is well prepared to tackle them. Their point of agreement is that, if not severely ill, the system's chronic ailments?particularly laggardness?must be addressed if it is to respond satisfactorily to rapid social, political, environmental and economic changes on a global scale.
Keywords: Antarktis; Antarktistraktaten; miljøvern; politikk

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern

Legitimacy of the Antarctic Treaty System: is it time for a reform? - Yermakova, Yelena (The Polar Journal, 2021)
The Antarctic Treaty System (ATS) has governed the Antarctic for the last six decades ensuring it to be a place of peace and scientific cooperation. Like any institution, the ATS exists in order to solve collective action problems through coordination and the creation of norms. But how do we know if a particular institution is the right one to solve a specific problem or address issues regarding the governance of a region? And when is it time to replace or reform such an institution? To answer these questions, we need an account of institutional legitimacy. An assessment of the legitimacy of the ATS is necessary in order to determine whether it is worthy of being empowered through support, or if it is time to reform some aspects of it. Building on the account of legitimacy of global governance institutions proposed by Buchanan and Keohane, the paper assesses the legitimacy of the ATS and argues that it is time to reform some components of it. Specifically, the paper assesses the legitimacy of the ATS based on the following criteria: minimal moral acceptability; comparative benefit; institutional integrity; and accountability. The paper highlights the ATS? shortcomings based on these criteria and suggests reforms that will strengthen the legitimacy of the ATS
Keywords: Antarktis; Antarktistraktaten

Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap

Current logistical capacity is sufficient to deliver the implementation and management of a representative Antarctic protected area system - Hughes, Kevin A; Grant, Susie M (Polar Research, 2018)
Antarctica’s terrestrial ecosystems are vulnerable to impacts resulting from climate change and local human activities. The Antarctic Treaty System (ATS) provides for the designation of protected areas through the Protocol on Environmental Protection to the Antarctic Treaty. Unsystematic use of agreed management tools, including Antarctic Specially Protected Areas (ASPAs), has resulted in a protected area system lacking representation across the full range of Antarctic terrestrial ecosystems and Antarctic Conservation Biogeographic Regions (ACBRs). Systematic Conservation Planning (SCP) methods provide established mechanisms to fulfil ATS protected area designation goals. However, how would a continent-wide ASPA system be delivered should appropriate sites be identified using SCP or other methods? Although the rate of area protection has slowed recently, we show that newer Consultative Parties to the Antarctic Treaty are increasingly active as ASPA proponents and may have scope for further engagement with protected area management activities. Furthermore, all 16 ACBRs were found to be within the operational footprint of at least two Parties, indicating that this current logistical footprint could support the implementation and management of a continent-wide ASPA system. Effective management of a representative Antarctic protected areas system could be delivered through greater participation by those Parties with currently more limited protected area management responsibilities and greater use of remote-sensing technologies for protected area monitoring, where appropriate. Crucially, political will to implement an ASPA system identified through SCP approaches may be greater once a pragmatic means of delivery and effective management has been identified.
Keywords: Antarktis; Antarktistraktaten; biodiversitet; forvaltning; klimaendringer; menneskelig påvirkning; miljøvern; områdevern; økosystemer

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

The impact of human activities on wilderness and aesthetic values in Antarctica - Summerson, Rupert; Bishop, Ian D. (Polar Research, 2012)
There has been little progress in implementing protection of wilderness and aesthetic values in Antarctica since the coming into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998. This can in part be attributed to a lack of research defining these values and showing how they may be assessed. In 2009, a survey comprising 90 images of Antarctic landscapes was established on the Internet to canvass as wide a cross-section of people with an interest in Antarctica as possible on their perceptions of wilderness and their aesthetic preference. At the time of writing, over 337 respondents from 23 nationalities have taken part in the survey. Responses were analysed to determine the effect of human presence, both transient and as infrastructure, on perceptions of wilderness and aesthetic values. The analysis was in three parts: (1) all images combined; (2) images grouped by landscape type, derived from the Environmental Domains of Antarctica regionalization; and (3) 16 pairs of digitally manipulated images of which respondents were shown either an original image or one in which human presence had been either digitally removed or added. Responses to images grouped by landscape type show that coastal and ice-free areas are less valued both aesthetically and as wilderness than mountainous and ice-covered terrains. Signs of human presence were found to make images significantly less likely to be considered as wilderness and also reduced their aesthetic rating. This demonstrates that human impacts on these values are measureable. Keywords: Antarctica; Madrid Protocol; wilderness; aesthetic; values; photographs.
Keywords: Antarktis; Antarktistraktaten; estetikk; menneskelig påvirkning; miljøpåvirkning; miljøvern

Guest editorial—the 1959 Antarctic Treaty: reflecting on the 50th anniversary of a landmark agreement - Dodds, Klaus (Polar Research, 2010)
Commemorating a particular anniversary is always an arbitrary affair, an act of whimsy. After all, why acknowledge the 50th anniversary of someone or some event as opposed to the 48th? In terms of birthdays, we tend to celebrate each year as another rite of human passage. However, when it comes to events such as wars and diplomatic encounters, the media and political commentators like more substantial blocks of time: 10th, 25th, 50th, 75th and 100th anniversaries are particularly noteworthy. The year 2009 has proven no different in terms of representing a temporal marker for the 50th anniversary of the signing of the 1959 Antarctic Treaty. In December 2009 a so-called Antarctic Treaty Summit was held in Washington, D.C. to take advantage of not only such a milestone, but also “to highlight lessons learned about international governance ‘with the interests of science and the progress of all mankind’ ” (Antarctic Treaty Summit 2009, emphasis added).
Keywords: Antarktis; Antarktistraktaten; historie; internasjonal samarbeid; politikk

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

Norge i Antarktis - Børde, Haakon (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1977)
Keywords: Antarktis; Antarktistraktaten; Dronning Maud Land; historie; internasjonal; politikk

Naturressursene i Antarktis - Antonsen, Per (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser

Antarktis og den internasjonale havbunnsorganisasjon - Traavik, Kim (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; havbunnen; havrett; internasjonal; politikk; ressurser; rett

Forurensing av polarområdene? Et spørsmål om regulering av utviklingen - Sollie, Finn (Internasjonal politikk, 1972)
Keywords: Antarktis; Antarktistraktaten; forurensning; internasjonal; miljø; politikk; økologi

Inspections in Antarctica - Hanevold, Truls (Cooperation and Conflict, 1971)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; rett

The Antarctic Treaty consultative meetings : form and procedure - Hanevold, Truls (Cooperation and Conflict, 1971)
Keywords: Antarktis; Antarktistraktaten; forskning; internasjonal; politikk

Antarktis i sikkerhetspolitisk perspektiv - Skagestad, Odd Gunnar (Internasjonal politikk, 1971)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser; rett

The political experiment in Antarctica - Sollie, Finn (Bulletin of the Atomic Scientists, 1970)
General discussion of international cooperation in Antarctica. In special issue Antarctica since the IGY; international laboratory for science and diplomacy.
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; internasjonal rett; internasjonal samarbeid

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; rett

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Sætrykk
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Arktis og Antarktis : aktuelle problemstillinger - Sollie, Finn (Internasjonal politikk, 1968)
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap